A Secure Image Encryption Algorithm Based on Hill Cipher System - S.K. Muttoo; Deepika Aggarwal; Bhavya Ahuja (Institute of Advanced Engineering and Science, 2012)
We present a technique of image encryption based on Hill cipher system that provides better security than existing approach of Bibhudendra Acharya et al. by rendering the image content completely scrambled using multiple self-invertible keys, block shuffling and a new developed pel transformation. The Hill cipher algorithm is one of the symmetric key algorithms having several advantages in encryption. However, the inverse of the matrix used for encrypting the plain text in this algorithm may not always exist. Moreover this algorithm is susceptible to known plain text attack. Our proposed algorithm is aimed at better encryption of all types of images even ones with uniform background and makes the image encryption scheme more secure.